The Potential of Endophytic Fungi in Promoting Rice Plant Growth and Suppressing Blast Disease - Novia Dwi Putri; Anton Muhibuddin; Luqman Qurata Aini (University of Brawijaya, 2021)
Endophytic fungi are fungi that inhabit the internal tissues of plant and belong to a group of microorganisms reported to have beneficial effects on plants. In this study, three endophytic fungi isolated from rice plant tissue were identified as Trichoderma asperellum, Curvularia chiangmaiensis, dan Fusarium solani. These three fungi have the ability to produce IAA between 3.03 to 6.00 µg/mL. For phosphate solubility assay, all endophytic fungi showed a clear zone around the colonies in Pikovskaya medium and could dissolve phosphate in the range of 2.74 to 17.61 µg/mL. In addition, in vivo observations of the inoculation endophytic fungi can reduce the intensity of blast disease in rice plant. So that, it can be seen that the three fungal isolates can become plant growth promoting fungi and can also used as bicontrol agents for blast disease in rice plant.